Being Farrucas in El Puche: A dialogue on transfeminist resistances, with Ian de la Rosa - Platero Méndez, R. Lucas (Re-visiones, 2024)
This conversation between Ian de la Rosa and Lucas Platero addresses the transfeminist resistance found in Ian de la Rosa's film work, with characters at the crossroads of gender, race and social class. In his latest work, Farrucas, he portrays a group of teenage girls that embody Moroccan and Andalusian mix-race in the neighborhood of El Puche (Almeria), acknowledging their strategies to cope with a context that tells them that they do not know, and are not worth. In this dialogue, we also address the discussion on the politics of representation of trans people in films, and we value the contribution of trans people to this discipline.
Keywords: Intersectionality; mestiza; resistance; trans; transfeminism